2006
DOI: 10.1007/bf03022794
|View full text |Cite
|
Sign up to set email alerts
|

Oral sodium citrate increases nausea amongst elective Cesarean delivery patients

Abstract: Purpose: Historically, aspiration of gastric contents with subsequent pneumonia was a major cause of anesthesia-related maternal mortality. Before elective Cesarean delivery, gastric fluid can be neutralized with histamine-2 blockers or with oral sodium citrate. Although sodium citrate is commonly used, many patients dislike its taste. We designed this study to determine whether or not patients are more likely to experience nausea during Cesarean delivery when sodium citrate is administered preoperatively. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…A possible explanation of this finding might be the effect of propacetamol as itself or the effect of 0.1 g / 5 ml × 10 ampules of sodium citrate, a solution added to reduce injection pain of propacetamol. It is supported by a previous study result which reported that ingestion of sodium citrate induced nausea [27,28]. …”
Section: Discussionsupporting
confidence: 81%
“…A possible explanation of this finding might be the effect of propacetamol as itself or the effect of 0.1 g / 5 ml × 10 ampules of sodium citrate, a solution added to reduce injection pain of propacetamol. It is supported by a previous study result which reported that ingestion of sodium citrate induced nausea [27,28]. …”
Section: Discussionsupporting
confidence: 81%
“…The inconsistency between direct and indirect comparisons for rates of intra‐operative nausea and vomiting may have been due to differences in the way trials reported this outcome or variation in confounding factors, such as the use of sodium citrate, which may increase the rate of nausea , or prophylactic anti‐emetics that reduce the rate . Other factors that may have contributed to inconsistency include the dose of intrathecally injected local anaesthetic or adjuvants, the surgical approach or other local practices that may have influenced the risk of intra‐operative nausea but were unrelated to maternal hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…Not an RCT. Assessing women’s positions for GA Hong 2004 Study assessed interventions for reducing aspiration pneumonitis at caesarean section not for reducing nausea and vomiting Hunt 1989 Study assessed drugs given for analgesia, not for prevention of nausea and vomiting Husemeyer 1980 Study assessed interventions for reducing aspiration pneumonitis at caesarean section not for reducing nausea and vomiting Iqbal 2000 Study assessed interventions for reducing aspiration pneumonitis at caesarean section not for reducing nausea and vomiting Ishiyama 2001 Study assessed drugs given for analgesia, not for prevention of nausea and vomiting Jasson 1989a Study assessed interventions for reducing aspiration pneumonitis at caesarean section not for reducing nausea and vomiting Kang 1982 Study assessing drugs given for blood pressure control, not prevention of nausea and vomiting Kangas-Saarela 1990 Study assessing drugs given for blood pressure control, not prevention of nausea and vomiting Karamanlioglu 1995 Study assessed interventions for reducing aspiration pneumonitis at caesarean section not for reducing nausea and vomiting King 1998 Study assessing drugs given for blood pressure control, not prevention of nausea and vomiting Kjaer 2006 In this review, we are assessing the efficacy of medication given for the specific purpose of reducing nausea and vomiting at caesarean section. In this study, the medication is given for the purpose of aspiration prophylaxis, and the incidence of emetic side effects is being studied Kocamanoglu 2005 Study looked at prevention of postoperative nausea and vomiting after general anaesthesia for cesarean section not regional anaesthesia Lim 1991 Study assessed interventions for reducing aspiration pneumonitis at caesarean section not for reducing nausea and vomiting.…”
Section: Characteristics Of Included Studies [Ordered By Study Id]mentioning
confidence: 99%